A Comparative Study On The Mechanical Strength Of 3D-Printed Versus Heat Cured Denture Base Resins (Academia Journal of Medicine, 2026)
Background: Denture base resins play a critical role in the longevity and clinical success of  removable prostheses. Conventional heat-cured polymethyl methacrylate (PMMA) has long  been the material of choice; however, the advent of 3D printing technology has introduced  alternative materials with potential advantages in fabrication efficiency and customization.  Despite these benefits, concerns remain regarding their mechanical properties. Aim: To compare the mechanical strength of 3D-printed denture base resins with  conventional heat-cured denture base resins. Materials and Methods: This in vitro study was conducted using standardized rectangular  specimens fabricated from two groups: Group I – heat-cured PMMA denture base resin and  Group II – 3D-printed denture base resin. Each group consisted of equal numbers of samples  prepared according to manufacturer specifications. Mechanical strength was evaluated using  a three-point bending test on a universal testing machine to determine flexural strength.  The obtained data were statistically analyzed using an independent t-test, with the level of  significance set at p < 0.05. Results: The heat-cured PMMA group demonstrated higher mean flexural strength  compared to the 3D-printed resin group. The difference between the groups was found  to be statistically significant (p < 0.05), indicating superior mechanical performance of  conventional denture base material under the tested conditions. Conclusion: Within the limitations of this study, heat-cured denture base resins exhibited  greater mechanical strength than 3D-printed resins. However, 3D-printed materials offer  advantages in terms of fabrication and digital workflow, suggesting the need for further  advancements to enhance their mechanical properties for long-term clinical application.
Keywords: 3D printing, denture base resin, heat cured PMMA, flexural strength, mechanical properties